Status Gizi dan Status Perkembangan Balita Usia 12-36 Bulan : Nutritional and Development Status of Toddler Age 12-36 Months - Siscadarsih, Indraswari; Widyasih, Hesty (Poltekkes Kemenkes Palu, 2020)
Malnutrition can be caused by delays in growth in children, including the development of gross motor, fine motor, language skill, and personality. Nowadays, 43% of children in developing countries are feared to have developmental disorders, and only 30% of pre-school children with developmental disorders are identified earlier. This study aimed to determine the relation of nutritional status and developmental status of children aged 12-36 months in Puskesmas Jetis Kota Yogyakarta. The design of this study was cross-sectional. The target population was children aged 12-36 months with 84 samples which are obtained by consecutive sampling. Nutritional status was obtained from measurements of weight and height or length from the WHO Standard. Developmental observations using the Denver II test. The data analysis used is fisher’s exact test. The result is the majority of the subject were in good nutrition and in good development status. There was a correlation between nutritional status and the developmental status of children aged 12-36 months with p-value 0,001. Underweight children were more likely 13,8 risk to have suspect development status compared to those in well-nourished